(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: To assess the relevance and comprehensiveness of the proposed curriculum, examine stakeholder perspectives on curriculum effectiveness, and validate it using a developmental model framework. Design/Methodology/Approach: A qualitative research design was employed to explore the perspectives of stakeholders in Ghana’s hospitality sector. A focus group discussion with 30 participants, including faculty, industry experts, and students, was conducted to analyse the data. Thematic analysis identified key patterns and insights, guiding amendments through member checking to ensure validation and accuracy. Research Limitation: The focus group format had limited participants’ ability to share sensitive or critical feedback about existing curriculum structures, potentially affecting the comprehensiveness of validation insights. Findings: Stakeholder perspectives highlight the curriculum’s effectiveness in integrating technology, sustainability, and experiential learning, while striking a balance between theory and practice. These validate the curriculum using a developmental model framework, demonstrating its potential to enhance career readiness and industry adaptability while identifying areas for further improvement. Practical Implication: These insights guide educators and industry stakeholders in enhancing hospitality education, fostering a skilled workforce, and sustaining Ghana’s hospitality sector as a key economic driver. Social Implication: This creates a generation of hospitality professionals committed to environmental stewardship, cultural sensitivity, and social impact, contributing to Ghana’s broader sustainable development goals. Originality/Value: This study employs a developmental model framework to validate the curriculum, emphasising comprehensive skill development, instructor proficiency, and hands-on learning experiences.